GAMBARAN PEMERIKSAAN INSPEKSI VISUAL ASETAT SEBAGAI DETEKSI LESI PRAKANKER SERVIKS PADA WANITA PEKERJA SEKSUAL TIDAK LANGSUNG DI HOTSPOT Y KECAMATAN TENAYAN RAYA PEKANBARU - Ovinitha, Sarah; Fidiawati, Wiwit Ade; Sofian, Amru (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTCervical cancer is a malignancy in the epithelial cells of the cervix that can be prevented and detected earlier, but still ranks as the fourth most common cancer in women worldwide. Early detection of cervical cancer in developing countries such as Indonesia that was recommended by World Health Organization (WHO) is Visual Inspection with Acetic Acid (VIA). Indirect Female Sex Workers (FSW) have a higher risk of cervical cancer. The aim of this study is to reveal the results of VIA on indirect FSW at hotspot Y District Tenayan Raya Pekanbaru. The method of this research is descriptive observational. The study population was WPS-TL residing in the hotspot Y District Tenayan Raya Pekanbaru and the samples were taken with total sampling method. The results showed that among 44 FSWs, 17 people (38.6%) of them had acetowhite on the VIA examination (positive VIA). It is concluded that the majority of indirect FSWs at hotspot Y District Tenayan Raya Pekanbaru have a negative IVA results.Key words : Visual Inspection with Acetic Acid (VIA), Cervical Cancer, Indirect Female Sex Worker (FSW), Hotspot Y